Communicological and sociological features of discourse on European integrations in the Serbian daily press - Milutinović, Irina R (Sociološki pregled, 2018)
Based on the assumption that the mass media play a significant role in creating an image of the European Union, the aim of the paper is to determine, based on sociological and communication theoretical knowledge and methods, the main features of the discourse on the European integration in daily press in Serbia. Conducting content analysis and discourse analysis of 376 news items from the sample, we have identified the main characteristics of reporting about issues of European integration in the Serbian daily press: proactive approach to events; information deficit; nationalization of European topics; varied reporting quality; weak media initiative; emphasized informative and subdued mediating role of journalists; invisibility of Serbian citizens’ participation as actors in elaboration of European topics.
Keywords: the Republic of Serbia; media discourse analysis; daily press; EU integration